1993
DOI: 10.1002/em.2850210406
|View full text |Cite
|
Sign up to set email alerts
|

Genotoxicity analysis of N,N‐dimethylaniline and N,N‐dimethyl‐p‐toluidine

Abstract: N,N-Dimethylaniline (DMA, CAS No. 121-69-7) and N,N-dimethyl-p-toluidine (DMPT, CAS No. 99-97-8) belong to the N-dialkylaminoaromatics, a chemical class structurally alerting to DNA reactivity. Their applications may be industrial (dye and pesticide intermediates, polymerizing agents) and surgical (polymerization accelerators for the manufacture of bone cements and prosthetic devices), thus implying heterogeneous types of human exposure. Findings of carcinogenicity in rodents and some nonexhaustive genotoxicit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(11 citation statements)
references
References 25 publications
2
9
0
Order By: Relevance
“…This well agrees with our previous results where DMPT was able to slow down the cell cycle of osteoblastlike cells, with a reversible effect [20]. In contrast, other authors found that even a very low amount of DMPT is able to inhibit protein synthesis, causing both qualitative and quantitative changes in chromosomal arrangement [21] and even modifying the process of bone mineralization [22]. One can notice that a single assay method detects damage to a particular cell compartment or function only, while a complete description of the cell behaviour through various analysis methods is more informative.…”
Section: Discussionsupporting
confidence: 93%
“…This well agrees with our previous results where DMPT was able to slow down the cell cycle of osteoblastlike cells, with a reversible effect [20]. In contrast, other authors found that even a very low amount of DMPT is able to inhibit protein synthesis, causing both qualitative and quantitative changes in chromosomal arrangement [21] and even modifying the process of bone mineralization [22]. One can notice that a single assay method detects damage to a particular cell compartment or function only, while a complete description of the cell behaviour through various analysis methods is more informative.…”
Section: Discussionsupporting
confidence: 93%
“…Our hypothesis is supported by the evidence that N,N-dimethylaniline and N,N-dimethyl-ptoluidine which belong to the N-dialkylaminoaromatics, display a dose-dependent clastogenic effect (Taningher et al, 1993;Bauchinger et al, 1989;Salassidis and Bauchinger, 1990;Srivastava et al, 2004;Bomhard, 2003). According to the developmental stages of the embryo, this effect might have developed during the third week after conception when the intraembryonic mesoderm, endoderm and ectoderm form different layers.…”
Section: Discussionsupporting
confidence: 65%
“…It has been suggested that the residual DMPT concentration in cement mantles of retrieved cemented THJRs, even after 10 years post implantation, is high enough to be of concern,20 and, if the DMPT leaches out of the mantle, it may produce many deleterious effects in the patient, such as cytotoxicity of cell replication and damage to chromosomes 21–24…”
Section: Introductionmentioning
confidence: 99%